Pengaruh Pelatihan Terhadap Kinerja Melalui Motivasi Pada Karyawan PT PLN Unit Pelaksana Pengendalian Pembangkitan Tello - Fastabiqul Khaira; Syamsuddin Syamsuddin (Journal of Business Administration (JBA), 2023)
This research aimed to determine the effect of training on performance through motivation among employees of PT PLN Unit Pelaksana Pengendalian Pembangkitan Tello. The research used an associative research design. The sampling technique used was proportionate sampling with a total of 70 employees. Data analysis included tests for instrument validity and reliability, classica assumption tests, descriptive data analysis, inferential data analysis using T-test and F-testco efficient of determination analysis, path analysis, and Sobel test. The data was processed using SPSS for Windows version 25.0.Based on the research conducted by the researcher at PT PLN Unit Pelaksana Pengendalian Pembangkitan Tello, it was found that the training, performance, and employee motivation were excellent. The training significantly influenced performance, and it also had a significant effect on employee work motivation. Employee motivation had a significant effect on performance. The indirect effect of training on performance through motivation was smaller than the direct effect of training on employee performance, indicating that motivation mediated the Â relationship between training and performance improvement.